Menimbang Ulang Teologi Pembebasan dalam Islam: Asghar Ali Engineer tentang Keadilan, Kesadaran Kritis, dan Pendidikan - Fajar Afwan; Muhammad Tamamul Iman; Aisyah Puan Maharani (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
Islam, like other religions, encompasses two inseparable dimensions: the esoteric, which is transcendent and absolute, and the exoteric, which is structured, rational, and contextual. The challenge in contemporary reality lies in the predominance of normative, textual, and elitist approaches to religion, which often fail to adequately address the socio-cultural needs of humanity as a whole. This study seeks to advance a contextual theological approach within Islamic studies, an approach that bridges the transcendental values of religion with the lived realities of human existence. Employing a descriptive-qualitative method, supported by hermeneutical inquiry and critical analysis of religious texts in relation to their social contexts, the research demonstrates that a contextual theological perspective can reveal the humanistic dimensions of Islamic teachings that are frequently overlooked by purely doctrinal frameworks. The findings contribute positively to the development of Islamic studies that are more applicable and responsive to the challenges of the modern age. In this regard, the reconstruction of theological thought through a contextual approach emerges as an imperative in ensuring that Islam remains a religion of enduring relevance across time and place (salihun li kulli makanin wa zamani).